2022
DOI: 10.1021/acssuschemeng.2c05579
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Recyclable Nitrogen-Doped Mesoporous Carbon-Supported Ru Catalyst for the Reductive Amination of Levulinic Acid/Esters to Pyrrolidones

Abstract: A highly effective transformation from renewable biomass and its derivatives into high-value-added chemicals and biofuels is important and challenging. Herein, a N-doped mesoporous carbon (NMC)-supported Ru catalyst developed by an incipient wetness impregnation method was reported for the reductive amination of levulinic acid (LA)/esters with amines to Nsubstituted 5-methyl-2-pyrrolidinones. A complete conversion of LA with a 99.8% yield of N-hexyl-5-methyl-2-pyrrolidinone (HMP) was achieved over 0.05 mol % R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Finally, M2 was hydrogenated by NiCo@NC to form the BMP, which is the rate-determining step. This reaction mechanism is consistent with that of our previous report of the reductive amination of LA with n -hexylamine over Ru/NMC …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, M2 was hydrogenated by NiCo@NC to form the BMP, which is the rate-determining step. This reaction mechanism is consistent with that of our previous report of the reductive amination of LA with n -hexylamine over Ru/NMC …”
Section: Resultssupporting
confidence: 93%
“…It is worth noting that there are two obvious peaks in the CO 2 -TPD profile at around 92 and 567 °C, corresponding to weak and strong basic sites, respectively, which originate from N-containing groups in CoNi@NC, such as CN heterocycles and the pyridinic nitrogen-oxide. Our previous study found that the basic sites in the carbon support are conducive to the formation of negatively charged metals . Furthermore, it is reported that the N-derived base sites on Co@NC could play a similar role to base additives, which can not only inhibit the formation of polyamines or prevent the accumulation of products on the catalyst surface but also effectively facilitate the hydrogenation and reductive amination …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations